Endogenously increasing uncertainties and governance - Olivér Kovács (Transformation, Integration and Globalization Economic Research (TIGER), 2014)
This contribution argues that uncertainty is integrated into the modern economic systems; however its autochthonously increasing feature is puzzling and should be addressed in a more dedicated way. Behind the curtain of increasing uncertainty, we purport to demonstrate that at least the following intertwined and interrelated main building blocks can be deciphered that are contributing to the deepening global distribution of uncertainty in the advanced world by establishing a vicious circle: (i) increasing complexity; (ii) wicked characteristics of policies; (iii) heigthening role of psychological factors in economics; (iv) secularly declining innovativeness feeding into inequality which reinforces and maintains increasing uncertainties. We also shed light on some implication of increasing fundamental uncertainty on governance.
Keywords: H00; D80; O3; 330; uncertainty; complexity; wicked policies; techno-economic paradigm; innovation